2013
DOI: 10.4236/fns.2013.46084
|View full text |Cite
|
Sign up to set email alerts
|

An Environment Friendly, Low-Cost Extraction Process of Phenolic Compounds from Grape Byproducts. Optimization by Multi-Response Surface Methodology

Abstract: Due to their beneficial effects on human health, phenolic compounds are increasingly attracting the attention of scientists and researchers all over the world. The main interest is in the extraction process of those natural plant-originated compounds from fruits, vegetables and plant wastes, namely grape wastes, in which phenolic compounds are the most abundant secondary metabolites. This waste exploitation not only re-assimilates those byproducts into the food cycle, but also avoids major environmental proble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 40 publications
(54 reference statements)
5
21
0
1
Order By: Relevance
“…25 found that antiradical activity of N. sativa extracts increased proportionally to the polyphenol content with a linear relationship between radical inhibition and total polyphenols. Similar studies by 26,27,28 showed concentration-dependent radical scavenging activity of polyphenol extracts.…”
Section: Antiradical Activity Of N Sativa Extracts Against Dpph Radicalsupporting
confidence: 76%
“…25 found that antiradical activity of N. sativa extracts increased proportionally to the polyphenol content with a linear relationship between radical inhibition and total polyphenols. Similar studies by 26,27,28 showed concentration-dependent radical scavenging activity of polyphenol extracts.…”
Section: Antiradical Activity Of N Sativa Extracts Against Dpph Radicalsupporting
confidence: 76%
“…The optimal conditions maximizing TPC and AA, in our previous work [15] were 37˚C and 28 hours to obtain 0.52 g GAE/100g DM and 23% respectively. Herein, the optimal extraction conditions obtained for milled pomace were 88˚C and 5 minutes to acquire a TPC and FC of 1.4 g GAE/100g DM, a TMA of 21 mg/100g DM, a TC of 2.2 g/L, an AA of 28% and an AC of 433 mg AAE/L.…”
Section: Multiple Response Optimizationmentioning
confidence: 99%
“…The optimization of aqueous phenolic compounds extraction from milled grape pomace at moderate temperatures and relatively long periods of time [15], was followed by the investigation of the potential capacity of transition to higher temperatures and shorter periods of time in the aim of reducing the overall cost of the process. The optimal conditions maximizing TPC yield, previously found by Rajha et al 2013 in aqueous solution [15] were 47˚C and 30 hours to obtain 0.7 g GAE/100g DM. Herein, we obtained 1.65 g GAE/100g DM at 98˚C after 5 minutes.…”
Section: Effect Of the Extraction Parameters On Tpc And Fcmentioning
confidence: 99%
See 1 more Smart Citation
“…RSM was demonstrated to be a potent tool in optimizing experimental parameters maximizing numerous responses [11]. Central composite design, which is one of the most common designs, has been widely used to optimize phenolic compounds extraction from grapes [12] and grape pomace [13]. In classical extraction methods, the major parameters believed to affect the effectiveness of the procedure and the quality of the extracts are: temperature, contact time, extraction solvent, solid-liquid ratio, and particle size [14].…”
Section: Introductionmentioning
confidence: 99%